1996
DOI: 10.1007/bf00180813
|View full text |Cite
|
Sign up to set email alerts
|

Clinical phase I and pharmacokinetic trial of vinorelbine administered as single intravenous bolus every 21 days in cancer patients

Abstract: We have performed a high-dose clinical and pharmacokinetic trial with vinorelbine administered as a bolus injection every 21 days. The aim was to evaluate a schedule with longer treatment intervals than one week and to determine the toxicity pattern of such a schedule. A total of 13 patients (pts) with solid tumors (non-small-cell lung [3 pts], unknown primary [3 pts], mesothelioma [2 pts], colon/rectum, sarcoma, thyroid, head/neck and cervix [1 pt each]) were entered [9 male, 4 female, median age: 56 years (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
4
11
1
Order By: Relevance
“…The current study confirmed the high plasma clearance (CL), the large volume of distribution at steady state (V ss ) and long elimination half-life described in those researches [26][27][28][29] with 25 or 35 mg/m 2 short infusion or bolus injection. When dose was adjusted to be comparably equivalent, the calculated pharmacokinetic parameters in our study were consistent with those from a previous study by Schilling et al [29], such as C max plasma 676.6 ± 220.2 ng/mL, AUC inf plasma 623.3 ± 220.1 h ng/mL, CL plasma 1.74 ± 0.97 L/kg/h, V ss plasma 34.3 ± 11.2 L/kg, where six patients were administered vinorelbine by bolus injection of 35 mg/m 2 and the plasma concentrations were determined by HPLC-UV. However, the above mentioned values from plasma samples were apparently lower than those reported in Marty's study with 20 min intravenous infusion of vinorelbine at 25 mg/m 2 [26]: for C max blood 761.8 ± 185.4 ng/mL and AUC inf blood 1042 ± 392 h ng/mL.…”
Section: Pharmacokinetic Applicationsupporting
confidence: 92%
See 1 more Smart Citation
“…The current study confirmed the high plasma clearance (CL), the large volume of distribution at steady state (V ss ) and long elimination half-life described in those researches [26][27][28][29] with 25 or 35 mg/m 2 short infusion or bolus injection. When dose was adjusted to be comparably equivalent, the calculated pharmacokinetic parameters in our study were consistent with those from a previous study by Schilling et al [29], such as C max plasma 676.6 ± 220.2 ng/mL, AUC inf plasma 623.3 ± 220.1 h ng/mL, CL plasma 1.74 ± 0.97 L/kg/h, V ss plasma 34.3 ± 11.2 L/kg, where six patients were administered vinorelbine by bolus injection of 35 mg/m 2 and the plasma concentrations were determined by HPLC-UV. However, the above mentioned values from plasma samples were apparently lower than those reported in Marty's study with 20 min intravenous infusion of vinorelbine at 25 mg/m 2 [26]: for C max blood 761.8 ± 185.4 ng/mL and AUC inf blood 1042 ± 392 h ng/mL.…”
Section: Pharmacokinetic Applicationsupporting
confidence: 92%
“…Such discrepancy also appeared in other clinical trials [27,28] and it is noteworthy that these pharmacokinetic values were based upon blood concentration measurements. Since in vitro experiments showed that platelets are the main carrier in blood for vinorelbine and several clinical studies [9,13,29] reported that vinorelbine concentrations were about 1.9 times higher in blood than in plasma, parameter comparisons had to take into account the ratio of AUC blood /AUC plasma which averaged 1.8. This could be the leading cause for the differences of pharmacokinetic parameters among the clinical studies on vinorelbine administered intravenously.…”
Section: Pharmacokinetic Applicationmentioning
confidence: 99%
“…Renal clearance of vinorelbine is minor compared to nonrenal clearance: a mere 11% [19] to 14% [20] of the unchanged drug eliminated via urine after IV administration is reported in published works. The present study calculated CrCl according to the Cockroft-Gault formula, which is based on patients' creatininemia, gender, age, and body weight.…”
Section: Discussionmentioning
confidence: 92%
“…The use of blood [20] is an obvious benefit to nurses and patients: twice less volume of sampling and no sample processing to separate plasma. Furthermore, VRL concentrations being higher in blood, they reached later the analytical lower limit of quantification (LLOQ).…”
Section: Clinical Experiencementioning
confidence: 99%
“…Little, although controversial information was available on the VRL metabolism [5,17,20]. Since a different metabolism profile might have been observed between i.v.…”
Section: Introductionmentioning
confidence: 99%